Heritage - public and expert discourse in the process of heritigization - Kajda, Kornelia (Ex Novo: Journal of Archaeology, 2019)
The debate about “Who owns the past?” has been and still is the subject heated discussion in heritage studies. Deciding what should be protected and what needs special social and governmental attention triggers many questions which are often met with equivocal answers. This article concentrates on a phenomenon framed as heritagization in relevant scholarship. The first section is devoted to the situations in which experts notify the public about the importance of places and historical events. Four case-studies will be discussed. The first two will touch upon cultural and natural heritage sites (Jewish and German heritage in Poland and Rospuda Valley) and show how a group of experts can influence Polish society to build a positive atmosphere around neglected heritage in Poland. The next two case-studies (communist heritage in Poland and Białowieża Forest) present how the situation of conflict between experts and the public may influence the way in which heritage is understood by the society. The case studies will also show how the public renegotiates the meaning of heritage and designates what should be preserved.